A continuous luminescence assay for monitoring kinase activity: signalling the ADP/ATP ratio using a discrete europium complex. Issue 94 (13th November 2017) - Hewitt, Sarah H.; Parris, Jonathan; Mailhot, Romain; Butler, Stephen J.
Abstract : A stable Eu(iii ) complex is reported that binds reversibly to ATP and ADP, providing a ratiometric luminescent signal that enables the kinase-catalysed conversion of ATP to ADP to be monitored in real-time. Abstract : We report the application of a stable cationic europium complex[Eu.1] + in a continuous-read luminescence assay for kinase activity.[Eu.1] + binds reversibly to ATP and ADP in water, at neutral pH, in the presence of Mg 2+ ions, providing distinctive luminescence responses that permits the kinase-catalysed conversion of ATP to ADP to be monitored in real-time.